Gramsci’s “Modern Prince” and the Contingencies of Political Struggle - Roio, Marcos Del [UNESP]; Neres, Geraldo Magella (Brill Academic Publishers, 2023)
The Gramscian proposition of the “modern Prince”, like most of the concepts elaborated by Gramsci in the Prison Notebooks, has always been open to interpretative controversy. These exegetical controversies stem from two main factors: the fragmentary nature of the prison writings and the method of work employed by Gramsci. The aim of this article is to apply the methodological perspective of “social contextualism” to the understanding of the Gramscian concept of the modern Prince. There is a threefold advantage in applying this methodology to the reading of Gramsci’s political theory: 1) it allows one to grasp the unitarity between theory and practice in Gramscian political elaboration, linking the militant Gramsci with the theoretical Gramsci (the pre-prison and prison writings); 2) it allows one to identify how the theory of the party present in the “Lyon Theses” was maintained and further developed in the Prison Notebooks; and, consequently, iii) it further allows one to identify the proposition of the modern Prince as the most advanced development of a theory of the party that had already been conceived by Gramsci in the period before his imprisonment.
Keywords: Gramsci; modern Prince; political theory; revolutionary party